Recontos orais, matriz gesto-fala e deficiência intelectual: um estudo de casos - Nascimento, Danniele Silva do (2024)
This research aims is to understand the marks of authorship present in multimodal retellings, identifying the aspects that constitute this type of narrative produced by children with intellectual disabilities in their oral productions. As specific objectives, we set out to 1) analyze the linguistic-discursive strategies mobilized in the act of retelling in the interaction scenes; 2) analyze how gestures occur and point out the gestural multiplicity in the interactive scenes; and 3) analyze the engagement and attentionality scenes involved in the retelling process. To systematize this research, we adopted a case study as the methodological procedure. It is worth noting that studies with more than one case exist and can be called multi-case studies, in which the research focuses on two or more subjects or organizations (CARNEIRO, 2018). This case study is of an observational, interventional and qualitative nature with children with intellectual disabilities, in the initial years (1st, 3rd and 5th grade) of elementary school in a public school in the municipality of Alhandra - PB. As a theoretical framework, we used Perroni (1992), Brandão (2015), Diedrich (2020; 2023) and Cavalcante and Mandra (2010) to discuss narrative; and Mcneill (1982), Kendon (2000) and Cavalcante (2020) to discuss gesture and speech. To discuss Intellectual Disability, we turned to the following sources: AAMR (2006), Pessoti (1984, 1999), Tomaz et. al. (2017), Pereira et. al. (2015), Dias e Lopes de Oliveira (2013) and Garghetti et. al. (2013). These sources focus on the problem of ID in a humanistic and social context and not necessarily on the medical eventualities that these individuals may present. Furthermore, we also used as a basis other studies that also discuss multimodality in interaction scenes, such as Ávila-Nóbrega (2023; 2017). Our observations allowed us to see that the children were able to creatively develop their multimodal oral retellings when they relied on playful supports such as puppets and drawings. These resources allowed them to create their own multimodal oral productions more autonomously, following a linear timeline (beginning, middle and end), with alternating narrator and character voices, for example. We also observed that the presence of the adult interactant is essential for the development of the Multimodal Oral Retelling, since it is through the adult's counterpoint that the child is able to progress. Aspects such as attentionality, engagement, linguistic referencing and other linguistic-discursive strategies (which we delimited in our research) were present in these children's productions, proving that narratives of this nature authored by children considered atypical can present the same complexity as productions by typical children.